Model(s) of the future? Overlay journals as an overlooked and emerging trend in scholarly communication - Thornton, Gail M.; Kroeker, Emily (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2022)
Overlay journals, a potentially overlooked model of scholarly communication, have seen a resurgence due to the increasing number of preprint repositories and preprints on coronavirus disease 2019 (COVID-19) related topics. Overlay journals at various stages of maturity were examined for unique characteristics, including whether the authors submitted their article to the journal, whether the peer reviews of the article were published by the overlay journal, and whether the overlay journals took advantage of opportunities for increased discovery. As librarians and researchers seek new, futuristic models for publishing, overlay journals are emerging as an important contribution to scholarly communication.